Generation of DelNS1 Influenza Viruses: a Strategy for Optimizing Live Attenuated Influenza Vaccines - Pui Wang (American Society for Microbiology, 2019)
ABSTRACT Nonstructural protein 1 (NS1) of influenza virus is a key virulence element with multifunctional roles in virus replication and a potent antagonist of host immune response. Deletion of NS1 (DelNS1) would create a safer and more extensively immunogenic live attenuated influenza virus (LAIV) vaccine. However, DelNS1 viruses are very difficult to grow in regular vaccine-producing systems, which has hampered the application of DelNS1 LAIV vaccines in humans. We have developed two master backbones of deleted-NS1 (DelNS1) viral genomes from influenza A or B viruses which contain novel adaptive mutations to support DelNS1-LAIV replication. These DelNS1-LAIVs are highly attenuated in human cells in vitro and nonpathogenic in mice but replicate well in vaccine-producing cells. Both influenza A and influenza B DelNS1 LAIVs grow better at 33°C than at 37 to 39°C. Vaccination with DelNS1 LAIV performed once is enough to provide potent protection against lethal challenge with homologous virus and strong long-lasting cross protection against heterosubtypic or antigenically distantly related influenza viruses in mice. Mechanistic investigations revealed that DelNS1-LAIVs induce cross protective neutralizing antibody and CD8+ and CD4+ T cell immunities. Importantly, it has been shown that DelNS1-LAIV can be used to enhance specific anti-influenza immunity through expression of additional antigens from the deleted-NS1 site. Generation of DelNS1 viruses which are nonpathogenic and able to grow in vaccine-producing systems is an important strategy for making highly immunogenic LAIV vaccines that induce broad cross protective immunity against seasonal and emerging influenza. IMPORTANCE Current seasonal influenza vaccines are suboptimal and low in immunogenicity and do not provide long-lasting immunity and cross protection against influenza virus strains that have antigenically drifted. More-effective influenza vaccines which can induce both humoral immunity and T cell immunity are needed. The NS1 protein of influenza virus is a virulence element and the critical factor for regulation of the host immune response during virus infection. Deletion of the NS1 protein is a strategy to make an optimal LAIV vaccine. However, DelNS1 viruses are very difficult to grow in regular vaccine-producing systems, hampering the application of DelNS1 LAIV vaccines in humans. We have generated a panel of both influenza A and influenza B DelNS1 LAIVs which are able to grow in regular vaccine-producing cells. These DelNS1 LAIV vaccines are completely nonpathogenic, exhibit potent and long-lasting immunity, and can be used to express extra viral antigen to induce cross protective immunity against seasonal and emerging influenza.